Motivation for Pregnant Women to Visit Antenatal Care (ANC) During the Covid-19 Pandemic - Riska Aprilia Wardani; Herlina Herlina (Universitas Islam Lamongan, 2021)
The current COVID-19 pandemic has caused many changes in various lives, including changes in health services. One of the health services that is important to be a concern is antenatal care. During 2020, there was a downward trend in the number of antenatal care visits in various regions in Indonesia. Several factors that influence the decline in antenatal care visits are the COVID-19 pandemic situation, including the implementation of various policies to overcome the spread of COVID-19 and the motivation of pregnant women to conduct antenatal care visits. The purpose of this study was to determine the motivations of pregnant women in conducting antenatal care visits during the COVID-19 pandemic. The research design used is descriptive. The population in this study were all pregnant women in the working area of the Sooko Health Center, Mojokerto Regency until August 2021 as many as 87 pregnant women. The number of samples in this study were 72 respondents who were taken using simple random sampling technique. The variable in this study was the motivation of pregnant women to visit antenatal care (ANC) during the COVID-19 pandemic which was categorized into strong motivation, moderate motivation and weak motivation. Data analysis using univariate analysis. From the results of the study, it was found that more than half of the respondents in this study had weak motivation in conducting antenatal care (ANC) visits during the covid-19 pandemic, namely 38 respondents (52.78%). Antenatal care visits are one of the important needs that must be a concern for pregnant women considering that through regular antenatal care visits, pregnancies experienced can be monitored and treated early if a risk of pregnancy disorders is identified so that pregnant women can undergo pregnancy without significant interference. Keywords : Motivation; Pregnant mother; Antenatal Care; Covid-19 pandemic